2005
DOI: 10.1080/10428190400013712
|View full text |Cite
|
Sign up to set email alerts
|

The role of interleukin-3 in classical Hodgkin's disease

Abstract: Classical Hodgkin's disease (HD) is a peculiar form of lymphoma characterized by a low frequency of tumor cells, the so-called Hodgkin (H) and Reed/Sternberg (RS) cells, embedded in a background of non-neoplastic (reactive) cells believed to be recruited and activated by H-RS cell-derived cytokines/chemokines. How these tumor cells can survive in such a seemingly hostile environment has confused researchers. We have previously identified interleukin (IL)-3 receptor (R) expression as a common feature of classic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 95 publications
1
32
0
4
Order By: Relevance
“…Because pDC are found to infiltrate a series of tumors, they are thought to play an important role for cancer immunity (2). Although the expression of GrB in tumor-infiltrating pDC has not been investigated so far, the main cytokines responsible for the induction of GrB in pDC, namely IL-3 and IL-10 (6), can be detected in the environment of neoplastic diseases (53,54). This suggests that GrB-secreting pDC in such an environment may be involved in suppressing the expansion of tumor-specific T cells, thereby contributing to a potential tumor evasion.…”
Section: Discussionmentioning
confidence: 99%
“…Because pDC are found to infiltrate a series of tumors, they are thought to play an important role for cancer immunity (2). Although the expression of GrB in tumor-infiltrating pDC has not been investigated so far, the main cytokines responsible for the induction of GrB in pDC, namely IL-3 and IL-10 (6), can be detected in the environment of neoplastic diseases (53,54). This suggests that GrB-secreting pDC in such an environment may be involved in suppressing the expansion of tumor-specific T cells, thereby contributing to a potential tumor evasion.…”
Section: Discussionmentioning
confidence: 99%
“…55 Increased expression of CD123/IL3Ra has subsequently been demonstrated in related malignancies, including MDS, chronic myeloid leukemia, and aggressive NHLs, among others. [56][57][58] The a subunit of IL-3R is a type I transmembrane glycoprotein (cytokine receptor superfamily) that co-dimers with CD131 (common b chain). Leukemic blasts seem to differentially express IL-3Ra compared with normal stem cells, 55 and this may relate to differential sensitivity to therapy.…”
Section: Novel Therapymentioning
confidence: 99%
“…Cytokines and lymphokines from CD4 + T cells can also activate CD8 + CTL, NK cells and macrophages, which have all been shown to be involved in tumor immunity (Adam et al, 2003;Gonthier et al, 2004;Ikeda et al, 2002;Peipp & Valerius, 2002;Smyth et al, 2002). Immunoregulatory cytokines such as IL-10 and TGF- play an important role in immune tolerance, and it seems that suppressor effect of regulatory T cells (CD4 + CD25 + ) on the development of tumor associated antigen-reactive lymphocytes is independent of cytokines (Aldinucci et al, 2005). Contributing to the complexity of the interactions between the reactive background and malignant cells, immune cells present in the local infiltrate have proved capable of modulating apoptosis and of inducing proliferation of tumoral cells via death receptors, cytotoxic granule liberation, and withdrawal of growth factors or production of immunosuppressive cytokines (Atkinson & Bleackley, 1995;Berke, 1995;de Visser & Kast, 1999;.…”
Section: Antitumoral Immunitymentioning
confidence: 99%
“…It has been estimated that EBV-specific T-cells might constitute up to 5% of circulating CD8 + T-cells (Hislop et al, 2002;Rickinson & Kieff, 2001 (Hsu et al, 1989) and IL-3 have demonstrated to present significant biological activity as growth and antiapoptotic factor for H/RS cells (Aldinucci et al, 2005). Serum levels of the receptor antagonist IL-1 (IL-1r ) are elevated in HL patients, patients with B symptoms have significantly lower levels of IL-1r than those without symptoms (Gruss et al, 1992).…”
Section: Role Of Virus In Hlmentioning
confidence: 99%